1988
DOI: 10.1210/jcem-67-1-131
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Interferon-γ in Human Endometrial Epithelial Cells in Vitro: Potential Local Growth Modulatory Role in Endometrium*

Abstract: We previously reported that recombinant interferon-gamma (IFN-gamma) induces HLA-DR (human lymphocyte antigen) molecules of the major histocompatibility complex in human endometrial epithelial cells in vitro. We now report that IFN-gamma inhibits the proliferation of human endometrial epithelial cells and a human endometrial carcinoma cell line (EnCa101AE). Human endometrial epithelial cells expressed HLA-DR molecules and underwent morphological changes when exposed to IFN. Furthermore, the proliferation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 21 publications
2
25
0
4
Order By: Relevance
“…Less immunohistochemical staining was observed in the proliferative phase, but as the men strual cycle progressed, more staining was observed, with the most IFN-y observed in the late secretory phase. This general increase in IFN-y throughout the normal men strual cycle may reflect the progressively increasing in flammatory state of the endometrium prior to normal menstruation and provides anatomical evidence for the hypothesis that IFN-y is involved in endometrial remod eling [18].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Less immunohistochemical staining was observed in the proliferative phase, but as the men strual cycle progressed, more staining was observed, with the most IFN-y observed in the late secretory phase. This general increase in IFN-y throughout the normal men strual cycle may reflect the progressively increasing in flammatory state of the endometrium prior to normal menstruation and provides anatomical evidence for the hypothesis that IFN-y is involved in endometrial remod eling [18].…”
Section: Discussionmentioning
confidence: 70%
“…Immunohistochemical studies have demonstrated macrophages and T cells in ectopic endo metrium (endometriosis) [6] and mRNA for IFN-y [7], Elevated numbers of macrophages and lymphocytes, and elevated cytokine levels have been reported in peritoneal fluid from women with endometriosis compared to those without disease [8][9][10][11][12][13][14], IFN-y, primarily secreted by acti vated T cells [15], differentially induces expression of the immune activation, antigen presentation marker, HLA-DR, on activated T cells and endometrial epithelium [ 16,17] and has been proposed to be involved in endometrial remodeling by inhibiting endometrial growth [ 18]. IFN-y has also been reported to adversely effect in vitro sperm motion parameters [ 19], fertilization [20], embryo devel opment [20], implantation events [21], and trophoblast proliferation [22], and may be responsible for the repro ductive failure of many women with recurrent sponta neous abortion [23].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Its role in endometriosis is unclear. However, although IFN-c is known to inhibit the proliferation of human endometrial epithelium, 14 the resistance of endometriotic cells to IFN-c-induced cell growth inhibition and apoptosis has been found to be a possible mechanism involved in the pathogenesis of endometriosis. 15 In addition, many studies have shown that the concentration of IFN-c is decreased in the peritoneal fluid of patients with endometriosis, 6,15,16 although results suggesting that the concentration does not differ between patients with endometriosis and controls have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…necessary for implantation. In several experimental models, it was shown that IFN-γ increases the endometrial epithelial barrier permeability of the basolateral surface and inhibits the proliferation of human endometrial cells [73,75]. IFN-γ expressed and secreted by T cells and lymphoid aggregates induces the human leukocyte antigen DR (HLA-DR) adjacent to the endometrial epithelium, which supports a role of IFN-γ in the induction of lympho-epithelial interactions [74].…”
Section: Possible Role In Conceptus Implantationmentioning
confidence: 97%